Placa cimentícia com resíduos de poliestireno expandido (EPS): estudo das propriedades físicas e mecânicas - Baptista Junior, Gercyr (2019)
A building’s sealing system has a fundamental importance, since it guarantees watertightness, protection, and thermal and acoustic insulation of constructions. The search for secondary raw materials, originated from industrial and domestic waste and with potential applications in civil constructions, is a current topic that has been generating several studies at both national and international levels. Although some of the waste are considered noble from the technical performance point of view, they end up being discarded in landfills, which considerably increases environmental impact. An example to be given is the Expanded Polystyrene residue (EPSR), to be used as an addition in civil construction materials, due to its properties, such as low density, thermal and acoustic insulation. This work proposes to evaluate the physical and mechanical performances of cement boards with different percentages of EPSR partially replacing the fine aggregate. Therefore, cement boards were fabricated, and mechanical and physical tests were performed. As the main conclusion of this study, it was found that it is possible to use EPSR as partial replacement of the aggregate to produce cement boards.